Evanescent Acoustic Waves From Subcritical Beam Illumination: Laboratory Measurements Near a Liquid-Liquid Interface - Osterhoudt, C.F.; Thiessen, D.B.; Morse, S.F.; Marston, P.L. (IEEE journal of oceanic engineering, 2008)
Grazing illumination of smooth sediments by acoustical beams generates a rapidly decaying evanescent transmitted wave. One approach to laboratory-based simulation of this process is described in this paper. Immiscible liquids are placed in contact, and the acoustical source is placed in the liquid having the lower sound speed. The orientation of the source transducer (a piezocomposite panel) is adjusted to give subcritical beam illumination. An acoustical field that has a significant evanescent component close to the interface is generated in the second liquid. The second liquid (water) has a lower density than the liquid containing the source of the acoustical beam so that the liquid containing the source is trapped below the simulated sediment (the water). This arrangement is convenient for hydrophone scans of the detailed soundfield in the simulated sediment. Above the center of the illuminated region, close to the interface, the field decays exponentially with a fixed phase. Adjacent to the intensely illuminated region there is a sequence of quasi-nulls associated with the interference of relatively weak evanescent and nonevanescent components of the transmitted wave. Similar features are found to be present in soundfields computed using the OASES, a widely used wave-number-integration-based algorithm.